TINJAUAN HUKUM TERHADAP EKSPLOITASI ANAK DI KOTA MAKASSAR - Nurmiati Muhiddin (El-Iqthisadi, 2022)
Abstract Exploitation of children is an act that uses children at will for their own interests which is carried out by families or other people and these actions interfere with the child's physical and mental development. In essence, child exploitation is an act that eliminates children's rights. This research was conducted based on literature studies with various journal and book references as well as some of the best and most updated articles. Library research (library research), namely research carried out by collecting data and theoretical basis. The position of the child as determined according to the 1945 Constitution is contained in Articles 34 and 28b which have a special meaning in the sense that children are legal subjects of the national legal system, who must be protected, cared for and fostered in order to achieve child welfare. Comprehensive government policies regarding child protection efforts in Indonesia are actually not satisfactory. Even though the existing laws and regulations have imposed legal sanctions on child trafficking which are regulated in the Criminal Code (KUHP) and Ministerial Decrees. Keywords: Child Exploitation, Human Rights, Legal Protection.